Znaczenie handlu zagranicznego we wzroście gospodarczym Korei Południowej w latach 1995-2005 - Drelich-Skulska, Bogusława (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The period of 1995-2005 has brought over double growth of GDP and the same growth of turnoverof foreign trade in the Republic of Korea, which became one of the world export leaders and itsparticipation in world export reached 3%, and that, by this largeness of the country, was a hugeachievement. Export and protectionist instruments used in import were important factors, which formed economic growth in the Republic of Korea between 1995 and 2005. The foreign trade policy has caused the change of the structure of fabricated assortment of goods. During the research period process, highly processed products gained considerable over superiority, over labour-consuming goods. Due to it, the structure of produced goods has been fitted for requirements of economies, and that has allowed to decrease the cost of fabricating, achieve benefits of scales, as well as take advantage of saved part of domestic product on investments. Besides, the efficiency of production and participation of services and industry in GDP has accrued, what is characteristic for highly advanced economies, however, agriculture has been pushed to the farthest back- ground. Simultaneously, the ratio of citizens life in the Republic of Korea has been ameliorated, the revenues have grown. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (16); 2008; nr 1193, s. 84-96